2012
DOI: 10.3340/jkns.2012.51.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Percutaneous Plasma Disc Coagulation Therapy for Lumbar Herniated Disc Diseases

Abstract: ObjectiveThis is prospective study of clinical outcomes of percutaneous plasma disc coagulation Therapy (PDCT) in patients with herniated lumbar disc disease (HLD) to evaluate the safety and efficacy in its clinical application and usefulness as a reliable alternative to microscopic discectomy.MethodsForty-six patients were enrolled in this study from April 2006 to June 2010. All patients had one-level HLD. Disc degeneration was graded on routine T2-weighted magnetic resonance Image (MRI) using the Pfirrmann's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Various classifications are used to evaluate pain and operative success in these patients such as VAS, Oswestry, and SF-36. 1,5,17 In the VAS evaluation of the patients who underwent plasma disk coagulation, it has been observed that improvement is more rapid than in conservative treatment. 1 All of our patients previously had 1 course of physiotherapy and experienced no significant radiculopathic decrease.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Various classifications are used to evaluate pain and operative success in these patients such as VAS, Oswestry, and SF-36. 1,5,17 In the VAS evaluation of the patients who underwent plasma disk coagulation, it has been observed that improvement is more rapid than in conservative treatment. 1 All of our patients previously had 1 course of physiotherapy and experienced no significant radiculopathic decrease.…”
Section: Discussionmentioning
confidence: 97%
“…Although microdiscectomy is the best surgical method, complications have been reported at a rate of 2% to 14%; these typically include instability, facet distortion, and spinal injuries in spinal ligaments, spinal muscles, and during laminectomy. 1 In lumbar steroid injections and foraminal injections, the pain stops at first, but long-term results are reported to be poor. 11 Other methods are nucleoplasty, intradiscal electrothermal therapy, chemonucleosis, and the latest one, percutaneous laser disk decompression.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations